Mindfulness for mediating the relationship between self-control and alexithymia among Chinese medical students: A structural equation modeling analysis - Liu, Chong; Cui, Can; Sznajder, Kristin K.; Wang, Jiana; Zuo, Xiaoxuan; Yang, Xiaoshi (Frontiers in Psychology, 2022)
Backgrounds: Medical students are prone to experience alexithymia due to academic work overload, which could increase the prevalence of mental illness such as anxiety and depression. Self-control may play an important role in the pathogenesis of alexithymia. However, the effect of self-control on both mindfulness and alexithymia has yet to be examined. The purpose of our study was to estimate the levels of alexithymia and to explore the relationships between alexithymia, self-control and mindfulness among medical students. Methods: From March 18th, 2021 to April 9th, 2021, a cross-sectional study with stratified sampling was carried out in China Medical University, Liaoning Province, China. A total of 1,013 medical students participated in this study. The questionnaires pertaining to the Toronto Alexithymia Scale (TAS-26) , the Five Facet Mindfulness Questionnaire (FFMQ) and the Self-control Scale (SCS) were used to assess students’ levels of alexithymia, mindfulness and self-control. We used hierarchical Multiple Regression (HMR) and structural equation modelling to explore the mediating role of mindfulness between self-control and alexithymia. Results: The mean score of alexithymia in medical students was 69.39±9.9. After controlling for confounders, males were more likely to experience alexithymia. Self-control, acting with awareness, describing, and observing in mindfulness were negatively associated with alexithymia (P<0.01). Mindfulness mediated the relationship between self-control and alexithymia (a*b=-0.06, BCa 95% CI: -0.09 to -0.031, Percentile 95% CI: -0.089 to -0.031). Conclusion: Chinese medical students experienced high levels of alexithymia. Self-control could directly attenuate alexithymia for medical students and indirectly affect alexithymia through the mediating path of mindfulness. Initiatives for self-control ability enhancement should be provided to medical students to combat alexithymia. And interventions on mindfulness training should be developed to prevent from alexithymia and promote mental health.